Classifying Prisoner Returns: A Research Note. (June 2016) - Gaes, Gerald G.; Luallen, Jeremy; Rhodes, William; Edgerton, Jared
Scholars often use administrative corrections data to identify the reasons that offenders return to prison, though such data usually obscure more complex processes underlying the cause of a return. This article describes the procedural nuances that make it difficult to record prison return paths and discusses these limitations. We focus on data elements and recording practices commonly found in administrative databases and discuss whether and how researchers may use these data to reliably identify/classify returns. We provide empirical demonstrations of these arguments using publicly available data and conclude that more extensive data are often needed to accomplish this objective.